OP0121 Lupus anticoagulant is associated with thrombotic events in healthy carriers: results from a prospective longitudinal study. (12th June 2018) - Ceccarelli, F.; Chistolini, A.; Perricone, C.; Rando, E.; Pirone, C.; Cipriano, E.; Leccese, I.; Massaro, L.; Morello, F.; Spinelli, F.R.; Alessandri, C.; Valesini, G.; et al.
Abstract : Background: Antiphospholipid syndrome (APS) is an autoimmune disease characterised by thrombotic events and/or pregnancy morbidity in combination with persistent positivity for antiphospholipid antibodies (aPL) [lupus anticoagulant (LA), anticardiolipin (aCL), anti b2 glycoprotein I (anti-β2GPI) in medium/high titers]. These antibodies could be identified not only in other pathological conditions (i.e. autoimmune diseases), but also in healthy subjects (aPL carriers). In this subset, the risk of developing thrombotic events or pregnancy morbidity ranges from 0% to 3.8%, and it is higher in subjects with LA positivity, triple positivity (LA+aCL+anti-β2GPI) and aCL positivity at high/medium titer. Nonetheless, 70% of aPL carriers described so far showed a concomitant autoimmune disease, being itself a risk factor for thrombotic events. Objectives: We longitudinally followed up a cohort of healthy subjects persistently positive for aPL to evaluate the risk of developing thrombotic events. Methods: Healthy subjects positive for aPL in at least 2 consecutive determinations ( aPL carriers ) were enrolled. Medical history was recorded and the following parameters were registered: presence of traditional risk factors (smoking, diabetes mellitus, hypertension, dyslipidemia, hormone therapy); obstetric history (infertility, miscarriages); family history of autoimmune and cardiovascular diseases with an early onset; recent infectious episodes. Laboratory evaluation was performed, including aCL IgG/IgM, anti-β2GPI IgG/IgM, LA, antinuclear antibody, C3/C4 serum levels, thrombophilia screening. All subjects were evaluated every 6 months. Results: We enrolled 47 aPL carriers (M/F 9/38, median age at first visit 45.5 years, IQR 17). Thirty-six subjects (76.6%) were aCL+ (30.5% at medium/high titer), 30 (63.8%) anti-β2GPI+ (36.7% at medium/high titer), 24 (51.1%) LA+. Thirty-one subjects (65.9%) were positive for more than one aPL and 12 (25.5%) showed a triple positivity. The aPL carriers were longitudinally followed up for a median of 60 months (IQR 48). Twenty-four subjects were treated with low dose aspirin (LDA) and 3 with hydroxychloroquine. During this observational period, 5 subjects were lost to follow-up and 5 became persistently negative for aPL after a median of 54 months (IQR 39). Considering the remaining 37 aPL carriers, 3 (1F, 2M) experienced a thrombotic event (2 arterial and 1 venous). This patients were treated with LDA at the time of the event and were all LA+. In one case, the episode was preceded by a flu-like event. Interestingly, the LA prevalence resulted significantly higher in the subjects experiencing thrombotic events in comparison with those who did not (p=0.0001). We observed an absolute risk of thrombotic events of 0.08 (CI: 0.02 to 0.2) and an incidence rate of 1.1 (CI: 0.3 to 2.9). Conclusions: In this prospective study, specifically designed to evaluate the incidence of APS related clinical manifestations in aPL positive healthy subjects, LA positivity resulted the most important risk factor of thrombotic events. Disclosure of Interest: None declared